A Window of Opportunity - Arthur Barker (Docomomo Journal)
The effects of climate change, resource depletion, and volatile economic circumstances require a reflection on current design approaches that can be gained through lessons from the original and mediated intentions of the Modern Movement. An important example can be found in South Africa before WW II, where the introduction of standardized building materials, particularly metal-framed windows, generated unique, mediated Modern Movement-inspired domestic interiors resulting from responses to a burgeoning industry, physical context, and functionalist attitudes to human activities. The clarion call of the Modern Movement for an architecture of economy, efficiency, and health underlined Le Corbusier’s “Cinq Points de l’Architecture Moderne” (Curtis, 1996, p. 175). This dictum was transmigrated to South Africa through the work of the zerohour Group formed in 1932. Unfortunately, the starkness of the ‘foreign’ architecture did not resonate with the general public, while interiors overheated and flat roofs leaked in the summer. In 1936, Iscor, a South African company, began assembling standardized metal window frames. Architects like Norman Eaton, Hellmut Stauch, and Robert Cole Bowen, sensitive to local contexts, utilized these metal window frames to create unique architectural interiors. The windows and associated modules not only provided an economical construction and structural logic through planning efficiency but generated more contextually and climatically related interiors, healthier internal environments, and fluid internal-external relationships. This article delves into the origins and impacts of the Modern Movement in Johannesburg and Pretoria, focusing on the transformative influence of the standard metal window. Then, the bioclimatic, technological, and spatial effects of these windows on residential interiors and their lasting legacy will be highlighted.